Antiproliferative activity of new derivatives of pyrazino[1, 2‐a]benzimidazole: Integrated cell‐based assay and computational studies with divalent magnesium, iron, and copper ions. Issue 10 (6th July 2022) - Rahimifard, Mahban; Jalalimanesh, Nafiseh; Movahed, Mahsa A.; Hadjighassem, Mahmoudreza; Pourahmad Jaktaji, Razieh; Bagheri, Zeinab; Pourahmad, Jalal; Zarghi, Afshin
Abstract: Magnesium, iron, and copper are three vital metals that play essential roles in cancer cell proliferation. This study aimed to evaluate the metal chelation of new derivatives of pyrazino[1, 2‐ a ]benzimidazole and investigate their antiproliferative properties. The density functional theory method has been employed to evaluate the complexation properties of new synthetic pyrazino[1, 2‐ a ]benzimidazole derivatives possessing the 4‐OMe, 2, 4‐dimethyl, and 3, 4, 5‐trimethoxy substitution on N‐2 phenyl ring with divalent magnesium, iron, and copper. The free energies for the water‐ligand exchange reactions were employed to investigate the thermodynamic stability, water exchange properties, and electronic properties in the gas phase. Natural population analysis was employed to estimate atomic partial charges, second‐order interactions between the filled and vacant orbitals, and the occupancies of the metals' valence s, p, and d orbitals. Among pyrazino[1, 2‐ a ]benzimidazole derivatives, the 3, 4, 5‐trimethoxy substituted pyrazino[1, 2‐ a ]benzimidazole shows better electron donor ability. This compound also reduced proliferation and increased the apoptosis of human glioblastoma cancer cells.